Pengaruh Kemampuan (Ability), Kebaikan Hati (Benevolence), Integritas (Integrity) Terhadap Partisipasi Pelanggan E-Commerce (Studi Pada Pelanggan E-Commerce di Surabaya) - Hendro Rumpoko; Epriliana Candra Dewi (Fakultas Ekonomi Universitas Yos Soedarso, 2022)
Transactions through e-commerce have a high potential risk. Therefore, the vendor's ability, benevolence, and vendor integrity are key factors in e-commerce. Surabaya as a developing city and only in the last five years has adopted e-commerce, of course it has some differences from developed regions which have been practicing it for a long time. These differences at least concern regulatory issues, legal instruments, and consumer behavior. In connection with the relatively new practice of e-commerce in Surabaya, an interesting phenomenon to study is the extent to which vendors' ability, benevolence and integrity towards e-commerce vendors and how they affect the level of customer participation. in e-commerce. The aims of this study were (1) to analyze the effect of the vendor's ability, benevolence, and integrity variables on e-commerce customers in Surabaya; (2) analyzing the effect of the vendor's ability, benevolence, and integrity variables on the level of participation of e-commerce customers in Surabaya; and (3) analyzing the effect of) on the level of participation of e-commerce customers in Surabaya. This research was conducted by taking a sample of e-commerce users in Surabaya. The main instrument for data collection was a questionnaire and was measured by a Likert scale. Questionnaires were sent to respondents via a mailing list. The number of respondents in this study were 152 respondents. The data analysis method used is the Structural Equation Model (SEM). Of the three predictor variables that affect vendor ability, benevolence, and integrity, it turns out that only vendor integrity has a positive and significant influence. Meanwhile, the predictor variables that influence customer participation in e-commerce, namely vendor ability, benevolence, and integrity, are only vendor integrity variables that have a positive and significant influence. Thus, vendor integrity is a very important variable in influencing e-commerce customer participation in Surabaya.